Determinan Indeks Pembangunan Pendidikan pada Daerah Tertinggal di Indonesia Tahun 2020 - Nurul Adhilah Busmah; Sugiarto Sugiarto (Seminar Nasional Official Statistics, 2022)
The quality of education in underdeveloped areas in Indonesia has not received much attention. The measurement of the quality of education as measured by various indicators has not been able to describe the overall quality of education in a region. At the international level, an index to measure the success of educational development has been established, namely the Education for All Development Index (EDI) or the Education Development Index (IPP). Calculations that are only carried out at the national level are considered not to be able to represent the assessment of educational development at the provincial and district/city levels considering that there are differences in characteristics in each region, especially in underdeveloped areas of Indonesia. This study aims to describe IPP in underdeveloped areas in Indonesia in 2020 and analyze the variables that affect IPP using multiple linear regression methods. The results show that 4 independent variables significantly affect IPP in underdeveloped areas in Indonesia in 2020, namely, the percentage of poor people, the percentage of internet access that supports learning, the ratio of student teachers, and the percentage of the last education of the head of the house at least senior high school.